Analysis of EMI noise of power electronics converter in photovoltaic system - Khanafee, Muhammad Akmal (2017)
Three phase inverter is one of method to balancing photovoltaic systems. Therefore, an investigation and design at efficient inverter may assist the system to be implemented efficiently. The consideration of EMI is very important. Entire power electronic device endure with Electromagnetic Interference (EMI). Electromagnetic Interference (EMI) are caused by the fast switching of the power switches and used in modulating the average voltage past a switching period. The electromagnetic interference (EMI) noise has cause systems inefficiency. The supply waveform or source with bunch if this noise will makes the load run improperly. The idea of this project is to reduce Electromagnetic Interference (EMI) from the inverter which is use to convert an output dc produce by photovoltaic source. Total harmonic distortion (THD) produces will reduces system efficiency considering bunch of noise that supply to the load. The electromagnetic interference (EMI) noise has cause In addition; the method used in this paper is the cheapest and affordable by the user. The suggested approach is verified through simulation studies.